Availability evaluation method for extended epidemic model and Markov chain based IoT - Xiaotong YE; Wenfei SUN; Shigen SHEN (Dianxin kexue)
To reflect the availability status of the Internet of things (IoT) under malware diffusion, an availability evaluation method of IoT based on the extended epidemic model SEIRD and Markov chain was proposed.According to actual states of IoT nodes, the classic epidemic model SIR was extended to establish the node state transition model SEIRD.From the dynamic change process of each state of IoT nodes, the dynamic probability equations of IoT nodes belonging to five states were constructed, the Markov matrix reflecting the state transition was obtained, and an availability calculation method of an IoT node was achieved.Taking typical star and cluster IoT topologies as examples, the availability evaluation methods of the whole IoT with different topologies were given.Experiments provide suggestions for administrators how to reasonably deploy the number of normal working nodes and routes.The research results have theoretical significance for improving IoT availability and promoting the successful IoT applications.